(untitled) (Conferencea, 2021)
This article provides information on the distribution entomophagous of aphis and their species composition in the intensive gardens of Andijan region. Four species of entomophagous species have been identified in the intensive garden. The most common species was the seven-pointed khan daughter, the relatively rare being the afelinus.